Hubungan Pengetahuan Konsumsi Makanan Tinggi Kalsium dengan Pengetahuan Pencegahan Kejadian Osteoporosis pada Masyarakat: Relationship Between the Knowledge of High Calcium Food Consumption and the Knowledge of Osteoporosis Prevention - Nursyifa, Salsabila; Tejoyuwono, Agustina Arundina Triharja; Putri, Eka Ardiani (Jurnal Abdi Keperawatan dan Kedokteran, 2026)
In osteoporosis, the microarchitecture of bone tissue deteriorates, leading to a decrease in bone mass. Predisposing risk factors for osteoporosis include inadequate understanding of the need of consuming rich calcium foods and a lack of public awareness on osteoporosis and its early prevention. The purpose of this research is to find out how well people in Rusunawa Harapan Jaya, Pontianak, know how to avoid getting osteoporosis and how much calcium they should be eating. Researchers in this study used a quantitative correlational analytic technique with a cross-sectional design. A total of 157 people from the community were chosen at random to take part in the research. We used a survey and the bivariate analysis of Spearman's rho to quantify the components. The results showed that the residents of Rusunawa Harapan Jaya, Pontianak, possess good knowledge regarding high calcium food consumption and the prevention of osteoporosis. The Spearman's rho correlation test indicated a statistically significant value of 0.001 (sig<0.05; r= 0.267), signifying a positive correlation between knowledge of high calcium food consumption and knowledge of preventing osteoporosis.  Among the inhabitants of Rusunawa Harapan Jaya, Pontianak, there is a statistically significant correlation between the awareness of avoiding osteoporosis and the use of foods rich in calcium.